Contribution of hydroxyl radicals to the degradation of Acid Orange 7 by fly ash under ultrasonic irradiation. Issue 39 (20th August 2016) - Li, Guoting; Feng, Yanmin; Wang, Binbin; Wang, Minduo
Abstract: Ultrasonic irradiation (US) alone usually has comparatively low ultrasonic degradation efficiency for limited organic pollutants. In this research, fly ash, an industrial waste from thermal power plant, was used to assist ultrasonic degradation of Acid Orange 7, a common dye pollutant. The decolorization efficiency within 60 min by US alone, fly ash adsorption alone and the combined process were of 3.8, 41.5, and 76.7%, respectively. The contribution of hydroxyl radicals was investigated systematically by indirect iso-propanol quenching method. Although more dyes were degraded by hydroxyl radicals in fly ash-assisted US than in US alone, the contribution percentage of hydroxyl radicals in the former system was much lower than that in the latter system, being 24.8 and 53.4%, respectively. The results showed that pH had significant impact on the degradation efficiency of dye due to its influence on generation of hydroxyl radicals. The coexistence of chloride, sulfate, and nitrate anions inhibited the contribution of hydroxyl radicals. In comparison to fly ash, diatomite and tourmaline were capable of facilitating the generation of more OH radicals, while kaoline actually reduced the contribution percentage of hydroxyl radicals.